2020
DOI: 10.1029/2020ms002092
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Convective Aggregation Using the Tropical Moist Margin's Length

Abstract: On small scales, the tropical atmosphere tends to be either moist or very dry. This defines two states that, on large scales, are separated by a sharp margin, well identified by the antimode of the bimodal tropical column water vapor distribution. Despite recent progress in understanding physical processes governing the spatiotemporal variability of tropical water vapor, the behavior of this margin remains elusive, and we lack a simple framework to understand the bimodality of tropical water vapor in observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…A first study employing that model version for RCE simulations is presented in Beucler et al . (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first study employing that model version for RCE simulations is presented in Beucler et al . (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Differences between simulations on CPUs and GPUs relate to rounding errors emerging from re-association of mathematical expressions, mathematical approximations or contraction operators, and architecture-specific implementations of transcendental functions (Arteaga et al, 2014;Schär et al, 2020). A first study employing that model version for RCE simulations is presented in Beucler et al (2020).…”
Section: Model Descriptionmentioning
confidence: 99%
“…We present this paper as an investigation of the impacts land‐sea contrasts have on convective aggregation in a global configuration, and provide it as a useful addition to the growing literature on connecting idealized aggregation studies to the manifestation of real world convective organization (e.g., Arnold & Randall, 2015; Becker & Wing, 2020; Beucler et al., 2020; Bony et al., 2020; Hohenegger & Stevens, 2016, 2018; Müller & Hohenegger, 2020; Muller & Romps, 2018; Shamekh et al., 2020a; Tompkins, 2001a). We have shown that, whilst the shape and scale of aggregation change when a continentally sized island is included in an idealized RCE world, many of the features of aggregation remain the same, including its effects on the large‐scale environment.…”
Section: Discussionmentioning
confidence: 99%
“…(2022), and the shape‐based BLW method of Beucler et al. (2020). Tompkins and Semie (2017) developed the I org index for use in numerical models, based on statistical comparisons with a pure random process.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative metric for the degree of aggregation is essential for a thorough analysis, and several approaches have been developed in recent years, each of which focuses on particular characteristics of aggregated convection. Some of these methods include the Simple Convective Aggregation Index (SCAI) of Tobin et al (2012), which is based on the numbers of convective clusters within a region along with the average distances between clusters; the subsidence fraction method of Coppin and Bony (2015); an approach based on the spatial variance of moist static energy (Wing & Emanuel, 2014); the convective organization potential (COP) of White et al (2017); the morphological index of convective aggregation (Kadoya & Masunaga, 2018); the area-based convective organization potential method of Jin et al (2022), and the shape-based BLW method of Beucler et al (2020). Tompkins and Semie (2017) developed the I org index for use in numerical models, based on statistical comparisons with a pure random process.…”
mentioning
confidence: 99%